Meneroka peranan remaja tidak terkawal ke atas isu keluarga: ke arah memahami self discovery remaja keluarga disfungsi - Norulhuda Sarnon; Nor Jana Saim; Fauziah Ibrahim; Ezarina Zakaria; Suzana Mohd Hoesni; Salina Nen; Nasrudin Subhi; Mohd Suhaimi Mohammad; Khadijah Alavi; Chong, Sheau Tsuey (Penerbit Universiti Kebangsaan Malaysia, 2018)
There are many problems and conflicts in families that can jeopardize the development among them especially children. Previous literatures show the relationship between dysfunctional family and beyond control behaviour among children. However, the understanding on the self-discovery process is still under scrutiny; a process on how a child cope to their suffering experiences in dysfunctional family. It is believed that a teenager is the most affected in a dysfunctional family. Hence, the study aims to explore coping behaviour (explored through their roles in families) of uncontrolled teenagers on family issues. A total of 36 beyond control teenagers who were under court order and probation participated in the study. This qualitative study opted grounded approach and analytical tools; open, axial and selective coding were used during the analysis. The study found six patterns of roles of teenagers on family issues: (i) protecting, (ii) reconciling, (iii) self-separation, (v) rebelling and (vi) sacrifice. The discussion provided is to understand coping through the teenager’s' roles on family issues. Positive characteristics identified in beyond control teenagers were discussed to encourage self-discovery for better development. Suggested intervention for beyond controlled teenagers and dysfunctional family is generally discussed according the pattern of identified roles.